The golden geese fly the internet: some research issues in the migration of Irish professionals - Wickham, James (Economic & Social Studies, 1998)
A new research agenda is needed for the study of Irish "middle class" emigrants. Globalisation and information technology fragment the identity of the nation state and society. The migration of skilled labour is first and foremost determined by new global economic networks, linked to new hierarchies of knowledge production. However, knowledges vary in the extent to which they are globally applicable. Migration also involves the relationship between knowledge production and the national economy and how local enterprises actually use domestically produced knowledges. Finally, do individual actors' national identities become selfconscious "product differentiation" in the pursuit of a global career?
Keywords: Skilled labour; Emigration; Ireland; Knowledge economy